2008
DOI: 10.1590/s1413-86702008000300006
|View full text |Cite
|
Sign up to set email alerts
|

Parainfluenza virus infections in a tropical city: clinical and epidemiological aspects

Abstract: Human parainfluenza viruses (HPIV) are genetically and antigenically divided into types 1 to 4 [1]. HPIV-1 to HPIV-3 are major causes of acute respiratory infections (ARI), including lower respiratory tract infections, in infants and children. These three types of HPIV have been more extensively investigated than HPIV-4 [2-4]. All subtypes can cause a full spectrum of respiratory illness, including upper respiratory infections, croup, bronchiolitis and pneumonia [1,5]. Seasonal patterns of HPIV infections are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 36 publications
3
14
2
1
Order By: Relevance
“…In Fortaleza, Ceará, a study carried out between 2001 and 2006, 3070 nasopharyngeal aspirates were analyzed and 976 (31.8%) were positive for viral infection. Nevertheless, only 3.8% tested positive for HPIV 25 . In São Paulo, THOMAZELLI et al analyzed 336 respiratory samples and found 28 (8.3%) to be positive for HPIV-3 and two (0.6%) for HPIV-1 51 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In Fortaleza, Ceará, a study carried out between 2001 and 2006, 3070 nasopharyngeal aspirates were analyzed and 976 (31.8%) were positive for viral infection. Nevertheless, only 3.8% tested positive for HPIV 25 . In São Paulo, THOMAZELLI et al analyzed 336 respiratory samples and found 28 (8.3%) to be positive for HPIV-3 and two (0.6%) for HPIV-1 51 .…”
Section: Discussionmentioning
confidence: 93%
“…In Brazil, epidemiological studies have demonstrated the importance of viruses as etiological agents of respiratory disease 5,7,8,10,14,16,17,19,25,29,33,35,38,40,43,51,53,59,60 . However, because such studies are mostly focused on the most common respiratory pathogens (FLUAV, HRSV, HPIV, HRV and HAdV), the role of emerging viruses as etiological agents of respiratory disease among Brazilian children remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Spain, involving hospitalized children aged up to 14 years with acute respiratory tract infections, PIV infections accounting for 11.8% of the positive cases [30]. In a study from Brazil aiming to define the etiology of community-acquired pneumonia in hospitalized children younger than 5 years, PIV infections were detected in 3.81%, ranked third among the most dominant viral agents [31].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not our aim to describe the seasonality of individual viruses (previously described for some viruses 6, 9, 10 ), here we conduct a detailed analyses of the viral seasonal signatures to determine their temporal association to ARIs, their severity and associated mortality. Wavelet analyses were used to investigate cycles and changes in seasonality.…”
Section: Methodsmentioning
confidence: 99%